Bergerak di Tengah Banalitas Diskriminasi (Studi Mengenai Kader Anak Muda Dalam Menantang Eksklusivisme di Partai Politik Kota Malang) - Nanda Harda Pratama Meiji (Jurnal Studi Pemuda, 2016)
This paper examines about the dynamics of youth in a political party in Malang,  East Java. The proliferation of young people and political parties give us an important picture, especially in the middle of the political situation in Indonesia which is getting negative. Instead of become apathetic, the youth are joined actively in the context of practical politics. A political party that should be an inclusive place for anyone in it (including those of young people) precisely do exclucivity by the others. Some youth who come from minority group especially based on race, class, and gender have experience about discrimination by some people in that party. Using qualitative method with biography approach, there are 3 key informants who will told about their narration related to exclucivity by some people in the political party. Although these youth cadres have experience about  racism, class, or gender discrimination, they still seem to be trying to survive and instead fight with in their own way.  For these youth the tendency of discrimination must be opposed from within the party because they assume that as a young generation have enough capital to change the future of the party for a better way.